Andreev-spectroscopy study of unconventional superconductivity in MgB2:(La,Sr)MnO3 nanocomposite: III Международный семинар по микроконтактной спектроскопииХарьков, Украина, 8–11 сентября 2014 г. - Krivoruchko, V.N.; D’yachenko, A.I.; Tarenkov, V.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Unconventional high-temperature superconductivity in MgB2:La0:65Sr0:35MnO3 (MgB:LSMO) nanocom-posite has been found recently [Phys. Rev. B 86, 10502 (2012)]. In this report, the symmetry of the nanocom-posite superconducting order parameter and plausible pairing mechanisms have been studied by the point-contact Andreev-reflection (PCAR) spectroscopy. To clarify the experimental results obtained, we consider a model of a ferromagnetic superconductor, which assumes a coexistence of itinerant ferromagnetism and mixed-parity superconductivity. The Balian–Werthamer state, with quasiparticle gap topology of the same form as that of the ordinary s-wave state, fits the experimental data reasonably well. Utilizing the extended Eliashberg formalizm, we calculated the contribution of MgB2 in the total composite’s conductivity and estimated the magnitude of the electron–phonon effects originated from MgB2 in I–V characteristics of the composite at above-gap energies. It was found that distinctive features observed in the PC spectra of the MgB:LSMO samples and conventionally attributed to the electron–phonon interaction cannot be related to the MgB2 phonons. It is argued that the detected singularities may be a manifestation of the electron-spectrum renormalizations due to strong magnetoelastic (magnon–phonon) interaction in LSMO.